PKCδ stimulates macropinocytosis via activation of SSH1-cofilin pathway - Singla, Bhupesh (Cell Signal, 2018)
Macropinocytosis is an actin-dependent endocytic mechanism mediating internalization of extracellular fluid and associated solutes into cells. The present study was designed to identify the specific protein kinase C (PKC) isoform(s) and downstream effectors regulating actin dynamics during macropinocytosis. We utilized various cellular and molecular biology techniques, pharmacological inhibitors and genetically modified mice to study the signaling mechanisms mediating macropinocytosis in macrophages. The qRT-PCR experiments identified PKCδ as the predominant PKC isoform in macrophages. Scanning electron microscopy and flow cytometry analysis of FITC-dextran internalization demonstrated the functional role of PKCδ in phorbol ester- and hepatocyte growth factor (HGF)-induced macropinocytosis. Western blot analysis demonstrated that phorbol ester and HGF stimulate activation of slingshot phosphatase homologue 1 (SSH1) and induce cofilin Ser-3 dephosphorylation via PKCδ in macrophages. Silencing of SSH1 inhibited cofilin dephosphorylation and macropinocytosis stimulation. Interestingly, we also found that incubation of macrophages with BMS-5, a potent inhibitor of LIM kinase, does not stimulate macropinocytosis. In conclusion, the findings of the present study demonstrate a previously unidentified mechanism by which PKCδ via activation of SSH1 and cofilin dephosphorylation stimulates membrane ruffle formation and macropinocytosis. The results of the present study may contribute to a better understanding of the regulatory mechanisms during macrophage macropinocytosis.